1969
DOI: 10.1144/gsl.qjeg.1969.002.01.05
|View full text |Cite
|
Sign up to set email alerts
|

The sedimentation and geotechnical properties of the Cromer Till between Happisburgh and Cromer, Norfolk

Abstract: The cliff-section between Happisburgh and Weybourne, on the north Norfolk coast, provides one of the most representative exposures of glacial sediments in the British Isles and this sequence is now generally accepted as being the product of the Lowestoft Stage. The Cromer Till, as defined in the Geological Survey Memoir, forms the lowermost part of the glacial sequence and is composed of two tills separated by a layer of laminated silts and clays; these units may be termed as follows:Upper Cromer Till'] Lamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Banham (1988), Hart (1990) and Hart & Boulton (1991) have concluded that the glacial sediments were deposited on land, although they recognized that the associated thick fine sediment units are of glacio-lacustrine origin (Hart 1992). In contrast, several authors have concluded that some of the tills are waterlain and the meltwater sediments represent delta and lake-bottom deposits (Kazi & Knill 1969;Banham 1970Banham , 1988 1980; Lunkka 1988Lunkka , 1991Lunkka , 1994Hart 1992;Eyles et al 1989). Indeed Eyles et al (1989) considered the sequence to be of glacio-marine origin.…”
Section: Southern North Seamentioning
confidence: 99%
“…Banham (1988), Hart (1990) and Hart & Boulton (1991) have concluded that the glacial sediments were deposited on land, although they recognized that the associated thick fine sediment units are of glacio-lacustrine origin (Hart 1992). In contrast, several authors have concluded that some of the tills are waterlain and the meltwater sediments represent delta and lake-bottom deposits (Kazi & Knill 1969;Banham 1970Banham , 1988 1980; Lunkka 1988Lunkka , 1991Lunkka , 1994Hart 1992;Eyles et al 1989). Indeed Eyles et al (1989) considered the sequence to be of glacio-marine origin.…”
Section: Southern North Seamentioning
confidence: 99%
“…Where the recession of temperate glaciers reveals a surface of subglacially-deposited till or other unlithified sediment, it is not, as has been commonly supposed (Kazi and Knill, 1969), hard and overconsolidated, but extremely soft and with a high water content (Baranowski, 1975 ;Boulton and Paul, 1976) . This is not merely a feature of the glacier margin but has been found to occur subglacially some distance from the glacier front.…”
Section: Sediment Deformation Beneath Glaciersmentioning
confidence: 99%
“…A subglacial consolidation model It has been generally assumed (Rominger & Rutledge 1952, Harrison 1968, Legget 1962, Kazi & Knill 1969) that the consolidation pressures to which subglacial materials are subjected is merely given by the pressure due to the overlying ice column. Harrison (1958) has claimed to have deduced the maximum thicknesses of glacier ice which had overridden a series of lake sediments from determinations of their preconsolidation pressures.…”
Section: Consolidation Of Subglacial Tillmentioning
confidence: 99%